2011
DOI: 10.1371/journal.pone.0028365
|View full text |Cite
|
Sign up to set email alerts
|

SNP/RD Typing of Mycobacterium tuberculosis Beijing Strains Reveals Local and Worldwide Disseminated Clonal Complexes

Abstract: The Beijing strain is one of the most successful genotypes of Mycobacterium tuberculosis worldwide and appears to be highly homogenous according to existing genotyping methods. To type Beijing strains reliably we developed a robust typing scheme using single nucleotide polymorphisms (SNPs) and regions of difference (RDs) derived from whole-genome sequencing data of eight Beijing strains. SNP/RD typing of 259 M. tuberculosis isolates originating from 45 countries worldwide discriminated 27 clonal complexes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 62 publications
5
28
0
Order By: Relevance
“…Selection of a Heterogeneous Set of M. tuberculosis Beijing Genotype Strains-To cover the full spectrum of the genotype family, we selected 14 ancient and 14 modern Beijing strains from a previous selection of 259 M. tuberculosis strains (40). Furthermore, we included the successful modern Beijing strain B0/W148, that comprises one-fourth of the M. tuberculosis Beijing isolates in different parts of Russia (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Selection of a Heterogeneous Set of M. tuberculosis Beijing Genotype Strains-To cover the full spectrum of the genotype family, we selected 14 ancient and 14 modern Beijing strains from a previous selection of 259 M. tuberculosis strains (40). Furthermore, we included the successful modern Beijing strain B0/W148, that comprises one-fourth of the M. tuberculosis Beijing isolates in different parts of Russia (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular Typing Methods-M. tuberculosis Beijing strains were selected from a previously published selection of 259 Beijing strains (40). Fourteen ancient and 14 modern Beijing strains were included in the study to optimally represent the M. tuberculosis family.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolates of the Beijing family of M. tuberculosis are characterized by their increased ability to spread and cause disease and their increased association with drug resistance in comparison with the levels for non-Beijing strains (2). Because of this, many methods have been developed that are aimed at identifying and differentiating M. tuberculosis Beijing isolates (3)(4)(5)(6). There are several methods for identifying Beijing isolates, including spoligotyping, restriction fragment length polymorphism (RFLP) using IS6110 as a probe, or the presence of a copy of IS6110 in the dnaA region (7).…”
mentioning
confidence: 99%
“…Several recent studies have shown that analysis of single nucleotide polymorphisms (SNPs) in bacterial genomes provides a means of determining relatedness between epidemiologically linked isolates and tracking bacterial evolution over periods of months to years [12][13][14][15][16]. In particular, several studies have tracked the genetic changes that emerge during long-term colonisation of cystic fibrosis patients [17,18].…”
Section: Introductionmentioning
confidence: 99%